2015
DOI: 10.1371/journal.ppat.1004894
|View full text |Cite
|
Sign up to set email alerts
|

FCRL5 Delineates Functionally Impaired Memory B Cells Associated with Plasmodium falciparum Exposure

Abstract: Exposure to Plasmodium falciparum is associated with circulating “atypical” memory B cells (atMBCs), which appear similar to dysfunctional B cells found in HIV-infected individuals. Functional analysis of atMBCs has been limited, with one report suggesting these cells are not dysfunctional but produce protective antibodies. To better understand the function of malaria-associated atMBCs, we performed global transcriptome analysis of these cells, obtained from individuals living in an area of high malaria endemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
175
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(192 citation statements)
references
References 63 publications
12
175
0
Order By: Relevance
“…+ cells described in HCV-MC patients (7,39 2 TLM B cells (36,40), in agreement with our study. Importantly, FCRL5 expression was found associated with markedly compromised BCR signaling and Ab production and it was suggested that FCRL5 marks dysfunctional cells (36,40).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…+ cells described in HCV-MC patients (7,39 2 TLM B cells (36,40), in agreement with our study. Importantly, FCRL5 expression was found associated with markedly compromised BCR signaling and Ab production and it was suggested that FCRL5 marks dysfunctional cells (36,40).…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, FCRL5 expression was found associated with markedly compromised BCR signaling and Ab production and it was suggested that FCRL5 marks dysfunctional cells (36,40). Most of the genes that we identified differentially expressed between the two subsets of TLM B cells were also detected in the malaria studies, which compared TLM B cells to classical memory B cells.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We also observed involvement of T-bet + B cells in the response to HIV infection, as T-bet was rapidly induced in B cells during the acute phase and T-bet We and others have previously demonstrated an expansion of CD21 -B cell subsets induced by Th1-type human infections, including HIV, malaria, and hepatitis C (30,31,34,35,(60)(61)(62)(63), and expansion of a clonal CD21 -subset has been described during hepatitis B-and hepatitis C-associated mixed cryoglobulinemia (64)(65)(66). Interestingly, maintenance of expanded CD21 -cells in each of these infections appears to be dependent upon pathogen load (34,35,60,(67)(68)(69).…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, chronic lymphochoriomeningitis (LCMV) viremia is controlled to low levels only in the presence of T-bet + B cells via a chiefly IgG2a-dependent mechanism (6). We previously identified a subset of T-bet-expressing B cells in healthy human blood (26), and B cells expressing either TBX21 transcript or T-bet protein have been described in the context of autoimmune disease, chronic hepatitis C infection, and malaria infection (27)(28)(29)(30)(31), but the biological niche of this population in humans has not been defined.…”
Section: Introductionmentioning
confidence: 99%